Wireless communications and applications : First International Conference, ICWCA 2011, Sanya, China, August 1-3, 2011, Revised Selected Papers - Ott, Max; Seneviratne, Aruna; Sénac, Patrick (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering,, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the First International ICST Conference on Wireless Communications and Applications, ICWCA 2011, held in Sanya, China, in August 2011. The 43 revised full papers presented were carefully reviewed and selected from around 90 submissions and cover a wide range of topics as mobile ad hoc networks, sensor networks, network architectural design, network protocol design, local area networks, MAC, routing, and transport protocols, quality of service provisioning, reliability and fault tolerance issues, resource allocation and management, signal processing, medical imaging, data aggregation techniques, security and privacy issues, wireless computing and applications for wireless network as smart grid, agriculture, health care, smart home, conditional monitoring, etc.